Chitosan-wrapped gold nanocluster material and preparation method and application thereof
Through the combination of chitosan-encapsulated gold nanocluster material and labelless ECL immune sensor, the problems of insufficient sensitivity, high cost and complex operation in the existing AFB1 detection methods are solved, and the rapid, accurate and low-cost detection of AFB1 in traditional Chinese medicinal materials is achieved.
Patent Information
- Application Number
- CN202211719097.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-30
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2042-12-30
AI Technical Summary
The existing AFB1 detection method has problems such as insufficient sensitivity, high cost, complex operation and long time consumption, and urgently needs a detection method with high sensitivity, low cost and fast speed.
Using chitosan-encapsulated gold nanocluster material, gel-encapsulated metal nanoclusters were prepared by a simple one-step synthesis method, and combined with the construction method of label-free ECL immunosensors, the rapid and accurate detection of AFB1 was achieved.
It realizes ultra-high sensitivity detection of AFB1 in traditional Chinese medicinal materials (detection limit is 9.3×10-15g/mL), which is fast, accurate and low-cost, and solves the problems of insufficient sensitivity, high cost and complex operation in traditional methods.
Smart Images

Figure CN116213706B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of nanomaterial detection of AFB1, and particularly relates to a chitosan-coated gold nanocluster material and a preparation method and application thereof. Background Art
[0002] Aflatoxin belongs to the detection range of mycotoxins in traditional Chinese medicine. It is a general term for a class of compounds with similar structures, and has strong toxicity, carcinogenicity, mutagenicity and teratogenicity. Chinese medicinal materials are easily contaminated by fungi during planting, harvesting, processing, storage and transportation, thus producing toxic aflatoxins. In this family of toxins, aflatoxin B1 (AFB1) is the most toxic. The 2020 edition of the "Chinese Pharmacopoeia" stipulates that the content of aflatoxin B1 in 25 kinds of Chinese medicinal materials such as orange peel and its decoction tablets cannot exceed 5μg / kg. Therefore, it is crucial to be able to detect aflatoxin B1 sensitively, quickly and accurately. At present, a variety of analytical methods for detecting AFB1 have been developed, including: thin layer chromatography, ultra-high performance liquid chromatography, liquid chromatography-mass spectrometry, enzyme-linked immunosorbent assay and fluorescent immunoassay. However, these analytical methods have some limitations, such as the insufficient analytical sensitivity of thin layer chromatography; the need for sample pretreatment and high operating costs of chromatography and mass spectrometry; and the need for complex steps and easy inactivation of enzyme-linked immunosorbent assay, which is time-consuming. Therefore, a new method with high sensitivity, low cost and high speed is urgently needed to detect AFB1.
[0003] Label-free electrochemiluminescence (ECL) analysis has the advantages of being fast, simple and low-cost, and is very suitable for developing a fast and sensitive AFB1 detection method. The construction of the sensing interface is the key to developing new strategies for label-free ECL analysis, and materials with ECL properties are the core of assembling the sensing interface. Gold nanoclusters (AuNCs) have become an attractive class of ECL luminophores due to their unique optical and electrochemical properties, multifunctional molecular-like structures and biocompatibility. However, the combination of the two has the following disadvantages, which limit the application of AuNCs. First, the ECL quantum yield is relatively low and cannot meet the requirements of ultrasensitive detection; second, the purification of AuNCs requires a dialysis process, which is time-consuming, labor-intensive and costly; third, its surface lacks abundant binding sites for further construction; fourth, when AuNCs are directly modified on the electrode surface, the ECL signal is not stable enough. In order to overcome these problems, some solutions have been proposed. For example, a method of improving the ECL emission by incorporating silver on AuNCs under GSH protection. Or three mechanisms of pre-oxidation, electrocatalytic effect and aggregation-induced emission have been proposed to greatly improve the efficiency of ECL. However, the above method is relatively complicated and costly.
[0004] Therefore, it is particularly important to propose a method that is simple in operation, low in cost and can accurately determine aflatoxin B1 in traditional Chinese medicines. Summary of the invention
[0005] In view of the above problems, in a first aspect, the present invention provides a chitosan-coated gold nanocluster material, wherein the chitosan-coated gold nanocluster material consists of chitosan and AuNCs nanoclusters coated with the chitosan.
[0006] In a second aspect, the present invention also provides a method for preparing the chitosan-coated gold nanocluster material.
[0007] The preparation method comprises the following steps:
[0008] adding the glutathione solution into the chitosan solution to obtain a mixture solution;
[0009] Adding chloroauric acid solution to the mixture solution, and adding sodium hydroxide to adjust the pH of the mixture solution to a fixed value;
[0010] The mixture solution is reacted in a water bath, cooled to room temperature, centrifuged, washed, and then dispersed in water to obtain a chitosan-wrapped gold nanocluster material.
[0011] Further, the concentration of the glutathione solution is 50 mM, and the volume ratio of the glutathione to chitosan solution is 0.3:8;
[0012] The concentration of the chloroauric acid solution is 24.28 mM, and the volume ratio of the chloroauric acid solution to the mixture solution is 0.41:8.3.
[0013] Furthermore, the sodium hydroxide solution is used in an amount of 500uL and has a concentration of 1mol / L;
[0014] The concentration of the chitosan solution is 2 mg / mL.
[0015] Furthermore, the water bath reaction is carried out at 80° C. for 6 hours.
[0016] In a third aspect, the present invention proposes a method for constructing a label-free ECL immunosensor, the method comprising the following steps:
[0017] Step 1: pre-treating the working electrode and preparing AFB1 antibody-modified cit-GNPs;
[0018] Step 2: dropping the chitosan-coated gold nanocluster material onto the pretreated working electrode surface;
[0019] Step 3: Add cit-GNPs modified with AFB1 antibody and react at 4 °C for 9 h;
[0020] Step 4: Then add BSA dropwise and allow to react at 37°C for 40 min;
[0021] After the reaction in step 3 and step 4 was completed, the electrode was washed three times with PBS buffer.
[0022] Further, the volumes of the AFB1 antibody-modified cit-GNPs and the BSA were both 40 μL;
[0023] The BSA is 1% BSA dissolved in PBS buffer.
[0024] In a fourth aspect, the present invention also proposes a label-free ECL immunosensor constructed according to the construction method.
[0025] In a fifth aspect, the present invention proposes a method for detecting AFB1 using the label-free ECL immunosensor, specifically:
[0026] 40 uL of AFB1 standard solution with a concentration gradient was added dropwise to the label-free ECL immunosensor, reacted at 37° C. for 60 min, and then washed with PBS buffer, and the luminescence degree of the label-free ECL immunosensor was observed.
[0027] Furthermore, the PBS buffer is PBS buffer comprising 10 mM Na2HPO4, 1.75 mM KH2PO4, 137 mM NaCl, 2.65 mM KCl, and pH=7.4.
[0028] The chitosan-wrapped gold nanocluster material can be used in detecting AFB1 or in constructing a label-free ECL immunosensor.
[0029] Furthermore, the AFB1 is derived from various types of Chinese medicinal materials, including three categories: rhizomes, fruits and seeds, and animals.
[0030] Beneficial effects of the present invention:
[0031] The present invention utilizes the spatial confinement effect of porous materials to improve the ECL efficiency. This effect can not only accommodate the ECL luminophore in the pores, but also promote electron and mass transfer in the electrochemical process. The present invention prepares gel-encapsulated metal nanoclusters through a one-step synthesis method, which only requires a simple centrifugation step to solve the dialysis problem of metal nanoclusters in the preparation process, thereby solving the problem of high cost, time and labor consuming preparation of metal nanoclusters.
[0032] The present invention utilizes gel to prepare metal nanocluster materials, which can enhance the electrochemiluminescence of the materials. Firstly, due to the spatial confinement effect of the gel, the diffusion rate of free radicals generated during the electrochemiluminescence reaction can be reduced, including free radicals generated by the luminescent substance and the co-reactant in the reaction; secondly, the gel can prolong the life of the excited state oxidation products of the luminescent substance.
[0033] The metal nanocluster material prepared by the present invention has good biocompatibility, film-forming property and abundant binding sites, and is easy to modify biomolecules, thereby being used to construct a stable sensing interface. Based on this, a label-free electrochemiluminescent immunosensor can be assembled to achieve ultra-high sensitivity (detection limit of 9.3×10 -15 g / mL), rapid, accurate and low-cost detection. The constructed sensing platform can also be expanded to the analysis of other low-content toxic and harmful substances in traditional Chinese medicine, which is of great significance for the quality monitoring of traditional Chinese medicine materials.
[0034] Other features and advantages of the present invention will be described in the following description, and partly become apparent from the description, or understood by practicing the present invention. The purpose and other advantages of the present invention can be realized and obtained by the structures pointed out in the description, claims and drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0036] Figure 1 TEM images of AuNCs@CS prepared from chitosan solutions of different concentrations in Example 2 of the present invention are shown;
[0037] Figure 2 A schematic diagram showing the ECL luminescence intensity of AuNCs@CS prepared from chitosan solutions of different concentrations in Example 2 of the present invention;
[0038] Figure 3 A schematic diagram showing the ECL luminescence intensity of AuNCs@CS synthesized under different volumes of NaOH in Example 2 of the present invention is shown;
[0039] Figure 4 A schematic diagram showing the effect of different antigen-antibody incubation times on ECL signal intensity in Example 5 of the present invention is shown;
[0040] Figure 5The rheological diagram of AuNCs@CS prepared in Example 2 of the present invention is shown;
[0041] Figure 6 The FT-IR spectrum of AuNCs@CS prepared in Example 2 of the present invention is shown;
[0042] Figure 7 TEM images of AuNCs prepared in Example 1 and AuNCs@CS prepared in Example 2 of the present invention are shown;
[0043] Figure 8 The XPS graphs of AuNCs prepared in Example 1 and AuNCs@CS prepared in Example 2 of the present invention are shown;
[0044] Fig. 9 A schematic diagram showing the ECL luminescence intensity of AuNCs prepared in Example 1 of the present invention, AuNCs@CS prepared in Example 2, and AuNCs / CS obtained by physical mixing;
[0045] Fig.10 The ECL spectra of AuNCs prepared in Example 1 and AuNCs@CS prepared in Example 2 of the present invention are shown;
[0046] Fig.11 The IECL-E curves of AuNCs@CS prepared in Example 2 of the present invention under different gas environments are shown;
[0047] Fig.12 The figure shows the ECL signal graph obtained during 24 stable cycles of cyclic voltammetry scanning of AuNCs@CS prepared in Example 2 of the present invention under the voltage condition of 0 V - 2.1 V - 0 V;
[0048] Fig.13 The schematic diagram of the ECL immunosensor for measuring AFB1 in the present invention is shown;
[0049] Fig.14 The ECL luminescence intensity graph (A) and EIS graph (B) of different materials detected by the constructed AFB1 immunosensor in Test Example 4 of the present invention are shown;
[0050] Fig.15 The calibration curve diagram of detecting AFB1 with different antigen-antibody incubation times in Example 5 of the present invention is shown. DETAILED DESCRIPTION
[0051] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0052] In view of the problems existing in the detection of AFB1 in the prior art, the present invention proposes to synthesize chitosan-coated gold nanoclusters (AuNCs@CS) by a simple one-step synthesis method. The ECL characteristics of AuNCs@CS were explored by cyclic voltammetry (CV). Compared with AuNCs, AuNCs@CS has good ECL emission and stability. The possible ECL enhancement mechanism of AuNCs@CS was proposed. On this basis, a label-free ECL immunosensor for quantitative detection of aflatoxin B1 was proposed. The assembly process of the ECL immunosensor was characterized by ECL and electrochemical impedance spectroscopy (EIS). The optimal conditions for the determination of AFB1 were studied. The analytical performance of the constructed sensing platform was studied. Finally, the applicability of the proposed immunosensor for the determination of AFB1 was evaluated by detecting the AFB1 content in traditional Chinese medicine.
[0053] The above-mentioned synthesis method, label-free ECL immunosensor and its assembly process are described in detail below in conjunction with the examples.
[0054] The reagents used in the examples were all analytically pure, and the ultrapure water used in the experiments was obtained from a Milli-Q system. The detailed information of the chemicals, materials, and instruments involved are as follows:
[0055] Stock solution of chloroauric acid (HAuCl4): concentration 24.28 mM, obtained by dissolving 1.0 g HAuCl4-4H2O (Shanghai Reagent Company, China) in 100 mL ultrapure water and stored at 4 °C;
[0056] Trisodium citrate was purchased from Sinopharm Chemical Reagent Co., Ltd.
[0057] Double-sided polyimide tape (DSPT) was purchased from Kaizhen Company (Shenzhen, China).
[0058] Chitosan (CS) (95% deacetylated) at a concentration of 10 mg / mL was obtained by dissolving chitosan in 2% acetic acid solution and centrifuging at 4000 rpm for 10 min to remove insoluble matter.
[0059] Bovine serum albumin (BSA) was purchased from Shanghai Aladdin Reagent Company.
[0060] Aflatoxin B1 antigen and aflatoxin B1 antibody were purchased from Shanghai Shenggong Biotechnology Co., Ltd.
[0061] Aflatoxin mixed standards were purchased from the China Food and Drug Administration.
[0062] ECL was detected using a homemade ECL / electrochemical cell system, including: CHI 760E electrochemical workstation (Shanghai Chenhua) and RFL-1 luminometer (Xi'an Ruimai).
[0063] The EIS experiments were performed using a CHI 760E electrochemical workstation (Chenhua, China).
[0064] Transmission electron microscopy (TEM) images were obtained by HT7700 Exalens (Hitachi, Japan). The surface functional groups of AuNCs@CS were characterized by Vector-22 Fourier transform infrared spectrometer (Bruker Instruments, Billerica, MA) using KBr pellets in the scanning range of 4000–400 cm -1 .
[0065] X-ray photoelectron spectroscopy (XPS) was performed on an ESCALABMK II electron spectrometer (VG Scientific, UK) using Al Kα radiation as the X-ray source.
[0066] The ECL spectra were acquired using an ECL spectrum acquisition system consisting of a CHI 760D electrochemical workstation (Chenhua, China), a spectrometer (SpectraPro HRS-300, Teledyne Princeton Instruments, USA), and an EMCCD (Newton, Andor Technology, UK).
[0067] Example 1 Preparation of AuNCs
[0068] The preparation method of AuNCs is as follows:
[0069] The glutathione solution was added to the HAuCl4-4H2O solution at 25°C and stirred gently;
[0070] The mixed solution was then transferred to a sample bottle and reacted in a 70°C water bath for 24 hours.
[0071] After the reaction was completed, the reaction solution was cooled to room temperature and dialyzed with ultrapure water for 12 hours through a dialysis membrane (molecular weight cutoff = 1000 Da) to remove excess precursors. Finally, the AuNCs solution was obtained and stored in a refrigerator at 4 °C away from light.
[0072] Among them, the glutathione solution was 50 mM, 2.4 mL; the HAuCl4-4H2O solution was 20 mM, 4.0 mL.
[0073] Example 2 Preparation of Au NCs@CS
[0074] AuNCs@CS was obtained by in situ growth of AuNCs in the presence of chitosan.
[0075] 2.1 The specific preparation steps are as follows:
[0076] First, 0.3 mL of glutathione (50 mM) was added to 8 mL of chitosan solution. Then 0.41 mL of chloroauric acid (24.28 mM) solution was added to the above mixture. The solution was adjusted to pH 6.0 by dropping 1.0 M sodium hydroxide solution. The solution was transferred to a water bath and reacted at 80 °C for 6 hours. After the solution was cooled to room temperature, the mixture was centrifuged and washed twice with water. Finally, it was dispersed in water and stored in a refrigerator at 4 °C away from light.
[0077] 2.1.1 In order to study the effect of chitosan on the ECL performance of AuNCs@CS, the ECL properties of the two synthesized materials were compared, and the concentration of chitosan added during synthesis was optimized.
[0078] The 10 mg / mL chitosan solution was diluted to obtain three chitosan concentrations of 2 mg / mL, 3 mg / mL, and 4 mg / mL, respectively. The volume of the diluted chitosan was 8 mL. Au NCs@CS was prepared according to step 2.1 and stored in a 4°C refrigerator away from light.
[0079] AuNCs@CS containing chitosan solutions of different concentrations were subjected to TEM (transmission electron microscopy) observation and ECL detection. TEM images of AuNCs@CS containing chitosan solutions of different concentrations are shown in Figure 2. Figure 1 As shown, Figure 1 A and B in the figure show the TEM images of AuNCs@CS with a chitosan concentration of 2 mg / mL at different magnifications, C and D show the TEM images of AuNCs@CS with a chitosan concentration of 3 mg / mL at different magnifications, and E and F show the TEM images of AuNCs@CS with a chitosan concentration of 3 mg / mL at different magnifications. Figure 1 It can be seen that in the presence of chitosan, the morphology of AuNCs@CS is a regular sphere. As the amount of chitosan increases, the morphology of AuNCs@CS gradually becomes elliptical. This observation shows that the concentration of chitosan has an effect on the morphology of AuNCs@CS. When the chitosan concentration is 2 mg / mL, the material morphology is more uniform and has better dispersion.
[0080] The ECL detection results of AuNCs@CS containing chitosan solutions with different concentrations are shown in Figure 2. Figure 2 As shown, from Figure 2 It can be seen that Figure 2 The horizontal axis is the detection voltage, and the vertical axis is the ECL intensity. Figure 2 It can be seen that when CS is 2 mg / mL, the ECL emission of AuNCs@CS is the strongest. Therefore, 2 mg / mL is the optimal chitosan concentration for synthesizing AuNCs@CS.
[0081] 2.1.2 Optimization of pH value
[0082] The ECL emission intensity was investigated when the volume of NaOH added was 300μL, 400μL, 500μL, and 600μL. When the volume of NaOH (1M) exceeded 600μL (pH>6), white flocculent precipitates appeared in the solution. It may be that the over-alkaline environment affected the formation of the chitosan-GSH complex.
[0083] The different pH test results are as follows Figure 3 As shown, when the volume of NaOH added was 500 μL, the ECL emission was the strongest, and this volume was selected as the optimal synthesis condition.
[0084] Au NCs@CS was prepared according to the optimal chitosan concentration and optimal pH value screened in 2.1.1 and 2.1.2.
[0085] Example 3 Preparation of cit-GNPs combined with sodium citrate gold (cit-GNPs) and AFB1 antibody
[0086] 91 mL of ultrapure water was added to 5 mL of chloroauric acid (6 mM) solution. When the solution was boiling, 4 mL of sodium citrate (w / w, 1%) solution was added and the reaction continued for 2 hours, and then naturally cooled to room temperature to obtain cit-GNPs;
[0087] After centrifugation at 6000 r / min for 10 min to remove large cit-GNPs particles, the GNPs solution was adjusted to pH 8.0 with 0.1 M NaOH solution;
[0088] Preparation of AFB1 antibody-modified cit-GNPs (Ab-GNPs): 25 μL of 0.5 mg / mL AFB1 antibody was mixed with the above GNPs solution overnight to obtain Ab-GNPs solution (antibody-modified sodium citrate gold solution).
[0089] Modification was performed by electrostatic interaction, hydrophobic interaction and weak covalent interaction. 250 μL of 5% (w / w) BSA solution was added to the Ab-GNPs solution, and then the reaction was allowed to stand for 5 minutes. The Ab-GNPs were centrifuged at 12500 r / min for 40 minutes (Centrifuge 5430R, Eppendorf Centrifuge, Germany), the supernatant was removed, and the precipitate was dispersed in PBS buffer (0.01 mol / L, pH 7.4) containing 1% (w / w) BSA. The obtained Ab-GNPs were stored at 4°C.
[0090] Example 4 Label-free ECL immunosensor for detecting AFB1.
[0091] The working electrode was FTO conductive glass and was pretreated as described in reference (Shu et al., 2015a). A 6 mm diameter circular hole was punched in the conductive area of the FTO electrode using DSPT to serve as a reservoir for subsequent assembly.
[0092] The assembly steps are as follows:
[0093] First, 20 uL of AuNCs@CS was added to the surface of the FTO electrode and dried naturally. Then 40 μL of cit-GNPs modified with AFB1 antibody was added and reacted at 4 °C for 9 h. In order to avoid nonspecific binding of AFB1, 40 μL of 1% BSA dissolved in PBS was added to block nonspecific sites. The reaction was carried out at 37 °C for 40 min. After each step of the assembly, the electrode needed to be washed three times with PBS buffer. Finally, the BSA / Ab-GNPs / AuNCs@CS / FTO AFB1 immunosensor was successfully fabricated and can be used to detect the content of AFB1.
[0094] Example 5 AFB1 Detection
[0095] (1) AFB1 was detected using the AFB1 immunosensor constructed in Example 4. The detection method is as follows:
[0096] 40 uL of AFB1 standard solution with a concentration gradient was added dropwise to the AFB1 immunosensor, reacted at 37°C for 60 min (i.e., antigen-antibody incubation time), and then washed with PBS buffer.
[0097] Since AFB1 is soluble in PBS buffer, 40uL PBS buffer was used as a blank experiment. The difference (ΔI) of the ECL reaction signal in the absence and presence of AFB1 was used for the quantitative detection of AFB1.
[0098] Among them, PBS buffer is 10mM Na2HPO4, 1.75mM KH2PO4, 137mM NaCl, 2.65mM KCl, pH=7.4.
[0099] Specifically, the antigen-antibody incubation time of the AFB1 immunosensor was optimized. Figure 4 The luminescence signal of the AFB1 immunosensor after incubation with antigen at different time points is shown. Figure 4 As shown in the figure, as the reaction time increases, the ECL emission intensity of the sensor continues to decrease and gradually stabilizes after 60 min, indicating that the antibody and antigen react completely. Therefore, 60 min is selected as the optimal reaction time for antigen incubation in this example.
[0100] Test Example 1 Characterization of AuNCs@CS
[0101] (1) The rheological properties of Au NCs@CS prepared in Example 2 were tested.
[0102] The storage modulus G' (elasticity of the reaction material) and loss modulus G" (viscosity of the reaction material) were used as indicators for investigation. The results are as follows: Figure 5 As shown in the figure, the horizontal axis is the angular frequency, and the vertical axis is the storage modulus G' / loss modulus G". It can be seen that the G' value is higher than the G" value, proving the successful formation of the Au NCs@CS gel state.
[0103] (2) The structure of Au NCs@CS prepared in Example 2 was studied by FT-IR spectroscopy. Figure 6 As shown, it can be seen that:
[0104] The characteristic absorption peaks are mainly: in the CS spectrum, located at 3412 cm -1 The broad peak at 2922 cm -1 It shows the stretching vibration peaks of CH, and CS still has these absorption peaks after synthesizing AuNCs@CS by hydrothermal reaction. The above experimental results prove that CS and AuNCs are successfully assembled.
[0105] Test Example 2 Morphological Characterization of AuNCs and AuNCs@CS
[0106] (1) TEM was used to observe the AuNCs prepared in Example 1 and the AuNCs@CS prepared in Example 2. The results are as follows: Figure 7As shown in the figure, A is the TEM morphology of AuNCs, B and C are the morphology of AuNCs@CS at different magnifications, from which it can be seen that AuNCs are well dispersed in water, with a morphology close to spherical and an average size of about 2 nanometers. However, in the presence of chitosan, the morphology of AuNCs@CS becomes a regular sphere with an average size of about 200 nm and a spacing of about 500 nm between materials.
[0107] (2) The reduction state of gold was analyzed by X-ray photoelectron spectroscopy (XPS). Figure 8 Center A shows the total XPS spectra of AuNCs and AuNCs@CS.
[0108] Compared with the total spectrum of AuNCs, the AuNCs@CS material still has the Au 4f peak, which should come from AuNCs. The binding energies of the 4f 7 / 2 orbital of 83.7 eV and 84.3 eV are attributed to Au(0) and Au(1), respectively.
[0109] Figure 8 Figures B and C show the XPS spectra of AuNCs and AuNCs@CS, respectively. It can be seen from the figure that the ratio of Au(0) / Au(1) is 0.92 and 1.07 in AuNCs and AuNCs@CS, respectively. According to literature reports, chitosan has a reducing effect on gold ions (Carbohydrate Polymers 134 (2015) 680–686.). Therefore, the content of Au(0) in AuNCs@CS material is higher than that in AuNCs.
[0110] Test Example 3
[0111] The AuNCs prepared in Example 1 and the AuNCs@CS prepared in Example 2 were dropped on the surface of the FTO electrode, and their characteristics were studied by cyclic voltammetry.
[0112] like Fig. 9 The IECL-E curves of AuNCs@CS, AuNCs / CS and AuNCs are shown, and the initial scanning direction is negative. An ECL peak at a potential of -1.8 V was observed in the negative potential scan. The ECL spectra of AuNCs@CS and AuNCs showed emission at about 700 nm ( Fig.10 ), Fig.10 Figure 2 is the ECL spectra of AuNCs and AuNCs@CS, indicating that the ECL emissions of AuNCs and AuNCs@CS are both related to AuNCs.
[0113] Under the same conditions, the ECL properties of AuNCs@CS were studied by cyclic voltammetry to explore the ECL effect of CS in AuNCs@CS. Fig. 9 As shown, it can be observed that the ECL intensity of AuNCs@CS is the strongest, the ECL intensity of AuNCs / CS material obtained by simple physical mixing is second, and the intensity of AuNCs is the weakest. This shows that CS can enhance the emission of ECL. On the one hand, CS, as a natural polymer, may follow a similar mechanism to enhance the ECL emission by reducing the diffusion of free radicals generated on the surface of gold clusters and prolonging the excited state lifetime of the excited state oxidation product AuNCs* in the CS gel. On the other hand, the ECL intensity of the material will gradually increase with the increase of Au(0) content (DOI: 10.1021 / acsami.7b02446). According to the above XPS results, the content of Au(0) in the AuNCs@CS material is higher than that of AuNCs. Therefore, the ECL of the AuNCs@CS material is further stronger than that of the AuNCs / CS material obtained by a simple physical mixing method.
[0114] In addition, in order to explore the luminescence mechanism of the material, the present invention studied the effects of air, oxygen and nitrogen environments on the ECL emission of AuNCs@CS.
[0115] The results are as follows Fig.11 As shown in the figure, each curve shows the I of AuNCs@CS using initial negative scan in different gas environments. ECL -E curve. Compared with the ECL peak in air environment, the intensity of ECL increases in oxygen environment and decreases significantly in nitrogen environment. These results indicate that O2 participates in the ECL reaction. O2 can be reduced to OOH at negative potential and then reacts with S2O8 2- Reaction to form SO4 .- , and then enter the chitosan gel, the gel can prolong the life of free radicals, making more SO4 .- With AuNCs - reaction, promoting the emission of ECL.
[0116] Possible mechanisms of luminescence are as follows:
[0117] AuNCs + e → AuNCs .-
[0118] S2O8 2- + e→ SO4 .- + SO4 2-
[0119] AuNCs - + SO4 .- → SO4 2- + AuNCs *
[0120] AuNCs* → AuNCs + hv
[0121] O2 + 2H2O + 2e → OOH - + OH -
[0122] OOH - + S2O8 2- → SO4 .- + HSO4 - + O2
[0123] like Fig.12 As shown in the figure, a stable ECL signal can be obtained in 24 cycles under the voltage conditions of 0 V - -2.1 V - 0 V. Therefore, AuNCs@CS exhibits excellent ECL stability and may be used in nanointerfaces for biosensing.
[0124] Test Example 4 Analysis of the performance of the label-free ECL immunosensor constructed in Example 4
[0125] (1) The schematic diagram of the ECL immunosensor for measuring AFB1 is shown in Fig.13 , the specific steps are as follows:
[0126] The AuNCs@CS was assembled on the treated FTO electrode surface and dried at a constant temperature in the dark.
[0127] cit-GNPs have good biocompatibility, large surface area, and conductivity, so AFB1 antibody was conjugated to cit-GNPs to form immunogold nanoparticles;
[0128] Since there are a large number of amino groups on the surface of CS, the AuNCs@CS modified FTO electrode can form an amino-rich film that can interact with Ab-GNPs to produce covalent Au-N bonds. Therefore, Ab-GNPs are immobilized on the surface of AuNCs@CS modified FTO electrode;
[0129] Finally, BSA was used to block the nonspecific binding sites on the assembled FTO electrode to form the BSA / Ab-GNPs / AuNCs@CS modified FTO electrode, i.e., label-free ECL immunosensor.
[0130] Under the optimal detection conditions, the ECL signal of the label-free ECL immunosensor was measured. In the presence of AFB1, the ECL signal was greatly reduced due to the formation of antibody-antigen complex. The ECL signals in the absence and presence of AFB1 were recorded as I0 and I, respectively. The reduced ECL signal ∆I (∆I = I0-I) can be used for the quantitative determination of AFB1.
[0131] (2) Characterization of the assembly process of label-free ECL immunosensor
[0132] In order to confirm the successful construction of the layer-by-layer assembly steps of the electrochemiluminescent immunosensor, the FTO electrode assembled in Example 4 was characterized using electrochemiluminescence signal graphs and EIS graphs. Fig.14 A is the ECL luminescence intensity diagram of different materials, and B is the EIS diagram of different materials; a is AuNCs@CS / FTO, b is Ab-GNPs / AuNCs@CS / FTO, c is BSA / Ab-GNPs / AuNCs@CS / FTO, and d is AFB1 / BSA / Ab-GNPs / AuNCs@CS / FTO.
[0133] from Fig.14 It can be seen that AuNCs@CS / FTO has electrochemiluminescence properties, and the modified FTO electrode has a more obvious impedance due to the non-conductivity of chitosan. When immunogold is modified in AuNCs@CS / FTO, the electrochemiluminescence signal is weakened and the EIS signal is enhanced because the antibody is a biomacromolecule and has an inhibitory effect on electron transfer. When Ab-GNPs / AuNCs@CS / FTO is titrated with BSA to close nonspecific binding sites, the electrochemiluminescence signal is further reduced and the EIS signal is further enhanced due to the inhibitory effect of protein on electron transfer. Similarly, when the modified electrode is further reacted with the target AFB1, the peptide produced by the specific binding of the antibody to the target reduces the ECL signal again, while the enhanced EIS signal indicates that the antigen-antibody binding is successful. The above results show that the electrochemiluminescence immunosensor is successfully assembled.
[0134] (3) Performance analysis of the AFB1 detection method proposed in Example 5
[0135] Under the conditions of the optimized antigen-antibody incubation time in Example 5 (ie, the reaction time was 60 min), the quantitative performance of the prepared label-free ECL immunosensor was evaluated by measuring the effect of the ΔI value on the AFB1 concentration.
[0136] The calibration curve for detecting AFB1 is shown in Fig.15 The immunosensor was 3.16 × 10 -14 -3.16 × 10 -12 The linear trend of ΔI and concentration was shown in the range of g / mL, and the linear regression equation was ΔI = 8847.157 + 616.2865× Log C (C in g / mL), with a linear correlation coefficient of 0.996. When the signal-to-noise ratio was 3, the detection limit of the immunosensor was 9.3x 10 -15The relative standard deviation of three replicates of AFB1 detection within one day was 0.04%, and the relative standard deviation of the days was 5.2% (n=5), which indicated that the label-free ECL immunosensor constructed in this work had good repeatability for the detection of AFB1.
[0137] The label-free ECL immunosensor was compared with other AFB1-based detection methods, and the results are shown in Table 1:
[0138] Table 1 Comparison of different methods for detecting aflatoxin B1
[0139]
[0140] As can be seen from Table 1, the sensor platform constructed in the present invention can achieve a smaller linear detection range, a lower detection limit, and does not require labeling technology, which means that we can quickly and quantitatively detect even trace amounts of AFB1.
[0141] (4) Selectivity of label-free ECL immunosensor
[0142] In order to verify the selectivity of the label-free ECL immunosensor assembled by the present invention, quantitative detection of the target is achieved through the specific binding of the antigen and the antibody, so a mixed standard is selected to perform the sensor specificity experiment. It is known that the concentration of the target AFB1 in the mixed standard is 1.08 ug / mL, while the total concentration of the interfering substances (AFB2, AFG1, AFG2) is 1.64 ug / mL. The concentration of AFB1 in the mixed standard is diluted to the linear range (AFB1=1.08×10 -13 g / mL), and a selectivity experiment was performed. A linear regression equation was constructed, and the test results are shown in Table 2.
[0143] Table 2 Quantitative analysis of aflatoxin B1 in mixed standards
[0144]
[0145] It can be seen from Table 2 that the sensor can quantitatively detect the target even in the presence of interferents, which proves that the sensor has good selectivity and accuracy.
[0146] (5) Determination of AFB1 concentration in Chinese medicinal materials
[0147] The practicality of the label-free ECL immunosensor constructed by the present invention was verified by detecting the concentration of AFB1 in Chinese medicinal materials. According to the provisions of the Chinese Pharmacopoeia on fungal detection in Chinese medicinal materials, 0.3 g of leech sample was accurately weighed, 0.06 g of sodium chloride was added, and then 1.5 mL of methanol (w / w%, 70%) was added and stirred at high speed for 2 min. Centrifuge at 4000 rpm for 5 min, accurately weigh 0.3 mL of supernatant, dilute to 1 mL, mix well, centrifuge at the same speed for 10 min, remove the precipitate, and obtain a stock solution.
[0148] The treated stock solution was diluted 1000-fold with 0.01 M PBS (pH 7.4). The results of the immunosensor are shown in Table 3.
[0149] Table 3 Quantitative analysis of aflatoxin B1 in leeches
[0150]
[0151] As can be seen from Table 3, the AFB1 content in leeches is 3.16×10 -14 -3.16×10 -12 There is a good recovery rate in the range of 1.3 g / mL (94.9%-98.8%), which shows that the matrix in the actual sample does not affect the detection results of the immunosensor for AFB1. The ECL immunosensor has good accuracy and practical use value.
[0152] Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent substitutions for some of the technical features therein; and these modifications or substitutions do not make the essence of the corresponding technical solutions deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. An application of a chitosan-coated gold nanocluster material in constructing a label-free ECL immunosensor or detecting AFB1, characterized in that: The chitosan-wrapped gold nanocluster material consists of chitosan and the chitosan-coated AuNCs nanocluster; and is detected by using a label-free ECL immunosensor; The construction method of the label-free ECL immunosensor is as follows: Step 1: pretreating the working electrode and preparing AFB1 antibody-modified sodium citrate gold cit-GNPs; Step 2: dropping the chitosan-coated gold nanocluster material onto the pretreated working electrode surface; Step 3: Add sodium citrate gold cit-GNPs modified with AFB1 antibody and react at 4 °C for 9 h; Step 4: Then add BSA dropwise and allow to react at 37°C for 40 min; After the reaction in step 3 and step 4 was completed, the electrode was washed three times with PBS buffer; The preparation method of the chitosan-wrapped gold nanocluster material comprises the following steps: adding the glutathione solution into the chitosan solution to obtain a mixture solution; Adding chloroauric acid solution to the mixture solution, and adding sodium hydroxide to adjust the pH of the mixture solution to a fixed value; The mixture solution is reacted in a water bath, cooled to room temperature, centrifuged, washed, and then dispersed in water to obtain a chitosan-wrapped gold nanocluster material.
2. The use according to claim 1, characterized in that: The concentration of the glutathione solution is 50 mM, and the volume ratio of the glutathione to chitosan solution is 0.3:8; The concentration of the chloroauric acid solution is 24.28 mM, and the volume ratio of the chloroauric acid solution to the mixture solution is 0.41:8.
3.
3. The use according to claim 1, characterized in that: The sodium hydroxide solution is used in an amount of 500uL and has a concentration of 1mol / L; The concentration of the chitosan solution is 2 mg / mL.
4. The use according to claim 1, characterized in that: The water bath reaction conditions were 80°C for 6 hours.
5. The use according to claim 1, characterized in that: The volumes of the AFB1 antibody-modified sodium citrate gold cit-GNPs and the BSA are both 40 μL; The BSA is 1% BSA dissolved in PBS buffer.
6. The use according to claim 1, characterized in that: The AFB1 is derived from various Chinese medicinal materials, including three categories: rhizomes, fruits and seeds, and animals.
7. A label-free ECL immunosensor, characterized in that: The label-free ECL immunosensor is constructed by the construction method according to any one of claims 1 to 5.
8. A method for detecting AFB1, characterized in that: The detection using the label-free ECL immunosensor according to claim 7 is specifically as follows: 40 uL of AFB1 standard solution with a concentration gradient was added dropwise to the label-free ECL immunosensor, reacted at 37° C. for 60 min, and then washed with PBS buffer, and the luminescence degree of the label-free ECL immunosensor was observed.
9. The method for detecting AFB1 according to claim 8, characterized in that: The PBS buffer is 10 mM Na2HPO4, 1.75 mM KH2PO4, 137 mM NaCl, 2.65 mM KCl, pH=7.4.
Citation Information
Patent Citations
Preparation method of electrogenerated chemiluminescence immunosensor and application of electrogenerated chemiluminescence immunosensor in detection of aflatoxin B1
CN112924662A